Web-based System for Preschool Children’s Academic Performance - Yusop, Nor Iadah; Chai , Jie Sheng; Saip, Mohamed Ali; Mohd Nor, Adiyati (Multidisciplinary Applied Research and Innovation, 2023)
Most preschools currently manually record children’s academic performances and this is not efficient as it is time-consuming and costly. In line with this, a system for preschool children’s academic performance can be a solution to such a problem. Hence the Web-based System for Preschool Children’s Academic Performance (PCP-WBS) was developed to facilitate the teachers in managing the children’s academic performance records. Therefore, PCP-WBS wanted to provide the respective kindergarten with an online management mechanism to improve traditional and physical methods of managing preschool children’s academic performance records. A Rapid Application Development (RAD) methodology was employed to develop the system. PCP-WBS is meant to facilitate the respective preschool teachers to record and manage the children’s academic performance. In addition, it also allows the parents to view and provide feedback on their respective children’s performance. Usability testing was conducted on the system. Though the PCP-WBS works as intended, some suggestions were also provided by the respondents, particularly for a better user experience.